Problem Solving Approach Based on Blended Learning on Trigonometric Comparison of Right Triangles on Mathematical Concept Understanding Ability - Yosafat Ardian Kristiarta; Wahyu Setyaningrum; Marsigit (Journal for Lesson and Learning Studies, 2023)
Mathematics is a mandatory subject for elementary to middle-level students. However, for some students, mathematics is a complex and scary subject. This research aims to analyze the influence of high school students' choice of mathematics learning strategies, mainly by determining the effectiveness of choosing a problem-solving approach through blended learning, especially the flipped class model, supported by a learning management system. This research uses quantitative research using a single experimental method or an experimental method with one group (single-group pretest-post-test design). The data collection technique in this research consists of 3 methods: observation, documentation, and tests. The data collection instrument uses a questionnaire sheet. The t-test method data analysis technique is known as the paired t-test. This data analysis process uses the help of RStudio® software version RStudio. Statistical tests and classroom observations show positive results, indicating that this approach is the right choice to help students learn mathematics. This means that there is an increased understanding of mathematical concepts by using a problem-solving approach based on a blended learning type flipped classroom assisted by LMS (Google Classroom) in class X MIA mathematics learning material on trigonometry comparisons in right triangles. The results of this research are that mixed learning (online and offline) in the flipped classroom type has a significant positive impact on increasing students' understanding of mathematical concepts, especially in teaching material on trigonometry comparisons in right triangles.